MANAJEMEN PERPUSTAKAAN SEKOLAH - Monaliza Monaliza; Rambat Nur Sasongko; Osa Juarsa (Manajer Pendididikan, 2017)
The purpose of this research was to describe the management of libraries in SMAN 1 Curup, specific objectives are to describe: the procurement plan library collections and the library service, procurement activities of the library collection, processing library collection, library services to visitors, monitoring and evaluation as well as follow further to the monitoring and evaluation activities. This research used descriptive qualitative method. The subjects of this study is the head of the library, librarian, Teachers, students, and school principals. The techniques for collected data were observation, interviews, and documentation. The data gotten by observation, interviews, and documentation.and data analysis techniques in the form of reduction, data display, and verification. The results showed the library management has been implemented properly.